Distribution of mangroves in Kuching Wetland National Park - Muhammad Anuar, Bin Aziz (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Mangrove forests have been exploited for long time to get their benefits and natural resources especially wood. Development, urbanization and constructions of coastal roads have been intensified resulted in the deterioration of mangrove areas. The current status of Kuching Wetland National Park (KNWP) mangrove forests is not well established. The objectives of this study were to determine the species distribution mangroves, assess the status of mangrove stands and determine the mangroves biomass in KWNP. Fourteen 20 x 20 m plots were established in there different vegetation types namely riverside mangrove forest, mixmangrove forest and kerangas forest. Diameter breast height (dbh) of trees  5 cm were enumerated in all plots. The dominant species in riverside vegetation, mix-mangrove and kerangas were Rhizophora apiculata, Avicennia alba and Eugenia spp., respectively. More than 50% of the enumerated trees were in the diamater class of 5 to 10 cm at dbh in all vegetation types. Height of trees were averaged at 8.9 m, 12.1 m and 8.5 m in riverside, mix-mangrove and kerangas vegetation, respectively. The highest biomass from riverside vegetation was Rhizophora apiculata at approximately 27,568 kg/ha followed by Xylocarpus granatum (7,459 kg/ha) and Rhizophora mucronta (3,166 kg/ha). Rhizophora apiculata also recorded the highest biomass in mix-mangroves with 33,047kg/ha followed by Ceriops tagal at 3,531kg/ha. Further study is needed to cover other parts of KWNP so that conclusvie results can be obtained and the status of the mangroves in the park can be assessed correctly.